Downregulation of miR‐1224 protects against oxidative stress‐induced acute liver injury by regulating hepatocyte growth factor. Issue 8 (8th March 2019) - Cheng, Wenting; Liu, Guo‐pan; Kong, Dehua; Huang, Wei; Sun, Ying; Zhao, Danmei
Abstract: Objective: To study the effect of microRNA‐1224 (miR‐1224) on hydrogen peroxide (H2 O 2 )‐induced oxidative stress injury in hepatocytes, and explore its underlying mechanism. Methods: L02 cells were treated with H2 O 2 (100 mmol/L) to establish the model of an oxidative stress injury in hepatocytes. Quantitative reverse transcriptase polymerase chain reaction was used to detect the expression of miR‐1224 and hepatocyte growth factor (HGF) in L02 cells. L02 cells were transfected with anti‐miR‐con (H 2 O 2 + anti‐miR‐con group), anti‐miR‐1224 (H 2 O 2 + anti‐miR‐1224 group), pcDNA3.1 (H 2 O 2 + ctrl group), pcDNA3.1‐HGF (H 2 O 2 + HGF group), si‐HGF and anti‐miR‐1224 (H 2 O 2 + anti‐miR‐1224 + HGF group), si‐NC and anti‐miR‐1224 (H 2 O 2 + anti‐miR‐1224 + ctrl group) by liposome method. Cells without any treatment were regarded as a negative control (NC) group. The protein expression of HGF in each group cells was detected by Western blot analysis. Cell viability and apoptosis of each group were detected by 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5 diphenyl tetrazolium bromide assay or flow cytometry, respectively. The interaction between miR‐1224 and HGF was measured by dual luciferase reporter gene assay. Results: The expression of miR‐1224 was enhanced in H2 O 2 ‐treated L02 cells and its knockdown alleviated H 2 O 2 ‐induced suppression of viability and promotion of apoptosis. HGF is a target of miR‐1224 and its overexpression abated H 2 O 2 ‐induced injury in hepatocytes. Moreover, silencing of HGF rescued the effect of downregulation of miR‐1224 on cell viability and apoptosis in H 2 O 2 ‐treated L02 cell. Conclusion: Downregulation of miR‐1224 could attenuate oxidative stress‐induced inhibition of viability and increase of apoptosis in hepatocytes by targeting HGF, which may provide a target for potential therapy of acute liver injury.